Enhanced waveform interpolative coding at low bit-rate. - Gottesman, O. (IEEE Transactions on speech and audio processing)
This paper presents a high quality enhanced waveform interpolative (EWI) speech coder at low bit-rate. The system incorporates novel features such as optimization of the slowly evolving waveform (SEW) for interpolation, analysis-by-synthesis (AbS) vector quantization (VQ) of the SEW dispersion phase, dual-predictive AbS quantization of the SEW, efficient parameterization of the rapidly-evolving waveform (REW) magnitude, and VQ of the REW parameter, a special pitch search for transitions, and switched-predictive analysis-by-synthesis gain VQ. Subjective tests indicate that the 2.8 kb/s EWI coder's quality exceeds that of G.723.1 at 5.3 kb/s, and it is slightly better than that of G.723.1 at 6.3 kb/s